THE IMPORTANCE OF FAIRY TALE PROBLEMS IN PRIMARY SCHOOL MATHEMATICS LESSONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
: The integration of fairy tale problems into primary school mathematics teaching provides a creative and engaging approach to developing students' problem-solving abilities, imagination, and mathematical thinking. This article explores the pedagogical significance of using fairy tale contexts in math instruction, highlighting how they enhance motivation, understanding, and long-term retention of mathematical concepts among young learners.